Effect of pump duty on natural frequencies and modes of its rotor vibration. Issue 1 (January 2021) - Yashchenko, A; Verbovyi, A; Rudenko, A
Abstract: This article deals with the development of more accurate models of high-performance pump units which work in a wide range of capacities. The pump operating range can sometimes reach from 20% Qr up to 130% Qr (Qr is the rated capacity). With changes of the pump duty, pressure difference between gap seals is changing as well. This leads to changes of hydrodynamic characteristics of gap seals. In particular, changes in radial stiffness of gap seals have an effect on the rotor dynamics. The task of creating the model has been performed in Modal Analysis subprogram of the ANSYS Workbench multifunctional software complex. Developed model demonstrates a dependence between pump duty and dynamics of the rotor. The nature and extent of influence of pump feed mode on the rotor dynamics has been determined. Data charts of this dependence have been obtained.